PVDF (Polyvinylidene Fluoride) polymer lateral chromatography membrane and preparation method thereof

By blending hydrophilic porogenic agent and surfactant with PVDF, a PVDF film with porous properties was prepared, which solved the problems of poor uniformity and low mechanical strength of nitrocellulose membrane in in vitro detection test paper, and achieved more Efficient protein retention and detection stability.

CN119455698APending Publication Date: 2025-02-18NANJING TECH UNIV +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411583018.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing nitrocellulose membranes have problems such as poor uniformity, low mechanical strength and poor chemical stability in in vitro testing papers, which are difficult to meet the needs of efficient testing.

Method used

A high molecular weight hydrophilic porogenic agent and surfactant were blended with PVDF, and a PVDF polymer lateral chromatography film with porous properties was prepared by steam-induced or non-solvent phase separation.

Benefits of technology

The prepared PVDF membrane has better mechanical strength, chemical tolerance and protein retention ability, and uniform porosity and pore size distribution. It is suitable for various dyeing applications and multiple immune detection. Replacing nitrocellulose membrane significantly improves the stability of detection. Sex and efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455698A_ABST
    Figure CN119455698A_ABST
Patent Text Reader

Abstract

The invention relates to a PVDF (Polyvinylidene Fluoride) polymer lateral chromatography membrane and a preparation method thereof, and according to the method, a large-aperture PVDF membrane is prepared by blending a hydrophilic additive with high molecular weight and PVDF powder. The method comprises the following steps: mixing PVDF powder with a hydrophilic pore-foaming agent (such as PVP, PEG and the like) by adopting a solution blending method, performing non-solvent induced phase separation (NIPS) to form a membrane, immersing the membrane into a coagulating bath for a period of time, transferring the membrane into deionized water for soaking, taking out the membrane after the solvent is completely removed, and drying the membrane at normal temperature to form the membrane. And immersing the membrane in a surfactant solution for a period of time, taking out the membrane, and naturally airing the membrane so as to obtain the PVDF flat membrane which has a macroporous structure, a good pore structure, hydrophilicity and protein adsorption performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of membrane technology, in particular to a PVDF polymer lateral chromatography membrane and a preparation method thereof. Background Art

[0002] Usually, the membrane used for in vitro test strips is nitrocellulose membrane, but the conventional nitrocellulose membrane has poor performance, uneven thickness, and poor strength and uniformity of the manufactured film. PVDF is a semi-crystalline and partially fluorinated polymer. It not only has the excellent thermal stability and antioxidant properties of fluorinated polymers, but also has certain chemical stability, excellent mechanical properties, protein adsorption properties, good processing properties and good solubility in polar solvents. These good properties make PVDF an important material for the preparation of porous membranes. Summary of the invention

[0003] The present invention aims at the problem of poor uniformity of nitrocellulose membrane and proposes a method of using PVDF membrane to replace nitrocellulose membrane. The method is to prepare a membrane that meets the basic requirements of colloidal gold in vitro detection by blending a high molecular weight hydrophilic porogen and a surfactant with PVDF and adopting a steam induced method or a non-solvent induced phase separation method.

[0004] A PVDF polymer lateral chromatography membrane has a porous property, a porosity of 50-82%, an average pore size of 4-8 μm, and a PVDF base membrane with a tensile strength of at least 0.3 MPa and an elongation at break of 10%, a porosity of at least 80%, and a capillary migration time of at least 180 s.

[0005] The chromatographic membrane also contains surfactants in its pores and / or on its surface.

[0006] The surfactant includes one or more of Tween 20, Tween 60, Tween 80, sodium dodecyl sulfate, polyethylene glycol octylphenyl ether, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium lauroyl sarcosinate, sodium methyl cocoyl taurate, and sodium polyoxyethylene lauryl ether sulfate in any weight ratio.

[0007] The preparation method of the above-mentioned PVDF polymer lateral chromatography membrane comprises the following steps:

[0008] Step 1: preparing casting solution: mixing PVDF powder and porogen, then adding solvent to dissolve to obtain uniform casting solution;

[0009] Step 2: The casting solution is scraped by a desktop scraping machine, and then a porous membrane is formed by phase inversion in a coagulation bath;

[0010] Step 3: The obtained porous membrane is placed in a solution containing a surfactant for immersion treatment, taken out and dried to obtain a chromatography membrane.

[0011] The casting solution comprises 10%-25% PVDF powder, 4%-12% porogen and 63-86% solvent by mass; the preferred range is 15%-20% PVDF powder, 6%-10% porogen and 75-80% solvent.

[0012] The porogen includes PVP K30 、PVP K60 、PVP K90 , PEG, glycerol or multiple thereof in any weight ratio.

[0013] The molecular weight range of the PEG is 200-20000.

[0014] The PVP K90 The content and the capillary migration time of water on the membrane surface are calculated by the following formula:

[0015] y=-3.25x 3 +68.125x 2 -485.75x+1365, where x is the additive content and y is the capillary flow time.

[0016] The solvent includes, but is not limited to, one or any combination of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), triethyl phosphate (TEP), cyclohexanone, and acetone.

[0017] The scraper thickness during the film scraping process is 100-500 μm, the film scraping temperature is 20-60° C., and the humidity is 20-98%.

[0018] The temperature of the coagulation bath is 30-90°C, and the solvent concentration is 20%-80%.

[0019] The solution containing the surfactant has a surfactant concentration of 0.1%-5% and also contains 2-10% glycerol, and the soaking time is 1-8 hours.

[0020] Application of PVDF polymer lateral flow membrane in in vitro diagnostic test strips.

[0021] Beneficial Effects

[0022] PVDF membrane replaces nitrocellulose membrane as the solid phase carrier membrane of in vitro test strips. Compared with nitrocellulose membrane, PVDF membrane has better protein retention ability. PVDF membrane has better mechanical strength and chemical resistance, and PVDF membrane is suitable for various staining applications and multiple immunoassays.

[0023] Traditional nitrocellulose membranes are brittle, have low mechanical strength, and poor uniformity. In addition, nitrocellulose has poor chemical stability and requires strict attention during transportation. It can spontaneously ignite when exposed to air and is very easy to burn and explode when exposed to open flames and high heat, which brings great uncertainty to the production of NC membranes. Using PVDF membranes instead of nitrocellulose membranes can avoid the above disadvantages.

[0024] The chemicals used are all PVDF, solvents, additives and surfactants which are common in the market, so they have the advantage of low cost.

[0025] The present invention uses PVDF membrane as an in vitro detection membrane for the first time, improves the membrane making process, and can prepare a uniform, stable and strong PVDF membrane with a capillary flow rate of 90-140s, a pore size concentrated between 4-12μm, and a protein adsorption amount close to that of commercial membranes, which meets the requirements for in vitro detection membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 : SEM photos of the surface and cross-section of the commercially prepared membrane.

[0027] Figure 2 : SEM photos of the surface and cross-section of the PVDF chromatography membrane of Example 1.

[0028] Figure 3 : SEM photos of the surface and cross-section of the PVDF chromatography membrane of Example 2.

[0029] Figure 4 : SEM photos of the surface and cross-section of the PVDF chromatography membrane of Example 3.

[0030] Figure 5 : SEM photos of the surface and cross-section of the PVDF chromatography membrane of Example 4.

[0031] Figure 6 : Pore size distribution of PVDF chromatography membranes of Examples 1-4.

[0032] Figure 7 : Tensile strength and elongation at break of the PVDF chromatography membranes of Examples 1-4.

[0033] Figure 8 : Porosity of PVDF chromatography membranes of Examples 1-4.

[0034] Fig. 9: Capillary flow time of PVDF chromatography membrane of Examples 1-4.

[0035] Fig.10 : PVDF chromatographic membrane additive PVP of Examples 1-4 K90 Fitting curve of content and capillary flow time.

[0036] Fig.11 : Protein adsorption capacity of PVDF chromatography membranes of Examples 1-4.

[0037] Fig.12 : PVDF chromatography membrane colloidal gold immunochromatography test strips of Examples 1-4 and Comparative Example 1. DETAILED DESCRIPTION

[0038] The invention discloses a method for improving the hydrophilicity and protein adsorption performance of a PVDF membrane, and replaces a traditional nitrocellulose membrane as a membrane for a colloidal gold in vitro test strip. The method comprises the following steps: dissolving PVDF powder and a polymer hydrophilic porogen in a polar solvent (such as DMAc) by a solution blending method, forming a membrane by a steam induction method or a non-solvent induced phase separation method, and then soaking the PVDF membrane in a surfactant solution for 1-8 hours, taking out the membrane, and placing it in the air to dry naturally.

[0039] The raw materials used in the present invention include:

[0040] Commercially available PVDF (6010) was purchased from Solvay Specialty Polymers. N-methylpyrrolidone (NMP) (>99.8%), polyvinylpyrrolidone K30 (PVP K30 )(Mw:40000), polyvinylpyrrolidone K60(PVP K60 )(Mw: 360000), polyvinyl pyrrolidone K90 (PVP K90 ) (Mw: 1300000). Polyethylene glycol 600 (PEG 600 )(Mw: 600). Tween 20, glycerol, rabbit anti-goat IgG and colloidal gold labeled goat anti-human IgG.

[0041] In a typical preparation method, the preparation method of the large-pore PVDF polymer membrane includes the following steps:

[0042] (1) Preparation of PVDF macroporous membrane

[0043] 8 g of PVDF 6010 was dissolved in 36 g of NMP, and then 4 g of PVP as a porogen was added under mechanical stirring at 60 °C. K90 With 2g PEG 600Add to the solution and keep stirring for 12 hours. After stirring, keep the solution at 60°C for 12 hours to degas the casting solution. Then pour the casting solution onto a clean glass plate and apply the film with a scraper (adjust the scraper height to 250μm and the speed to 1.2m·min -1 ). The glass plate was then immersed in a coagulation bath containing 60% NMP aqueous solution (volume fraction) at 60°C. After the phase separation process was completed, the membrane was transferred to a deionized water solution to wash away excess solvent, and then the membrane was taken out and dried naturally.

[0044] (2) Membrane Wetting Modification

[0045] 1 g of Tween 20 and 5 g of glycerol were dissolved in 96 g of deionized water and mechanically stirred at 37° C., and the PVDF membrane prepared in the above steps was immersed in the solution for 8 hours. The membrane was then taken out and dried naturally.

[0046] Characterization and testing methods include:

[0047] (1) Film tensile strength test

[0048] Edberg digital display push-pull force gauge HP-30N was used to measure the mechanical strength of the film. Each sample was cut into the same shape with a Japanese knife die, and the thickness of each sample was measured using a thickness gauge before testing. The sample was fixed at both ends of the sample holder and the sample was fixed at 5mm min. -1 The constant rate stretching (room temperature) was performed five times for each sample, and the maximum and minimum values ​​were removed to obtain the average data from the remaining measurement data.

[0049] (2) Membrane morphology characterization

[0050] The surface and cross-sectional morphology of the prepared PVDF membrane were observed by scanning electron microscopy (SEM). The dried membrane was cut into long strips, and the cross-section was frozen in liquid nitrogen and brittle fractured. The sample was attached to the electron microscope stage to observe its microstructure.

[0051] (3) Capillary migration time test

[0052] This experiment measures the capillary migration velocity of the prepared membrane by the following steps. The sample is cut into 2 cm wide and 6 cm long pieces, and deionized water is used as the migration medium. When the membrane contacts the deionized water, the timing starts when the water migrates 5 mm along the membrane surface, and stops when the water migrates to 4 cm from the membrane surface.

[0053] (4) Pore size distribution test

[0054] The pore size distribution of the PVDF membrane was tested by the gas-liquid replacement method. The PVDF membrane was cut into 2 cm square membrane pieces, soaked in isopropanol until completely wetted, and then tested by the instrument and the pore size distribution was calculated.

[0055] (5) Protein adsorption test

[0056] The membrane binding ability was evaluated using the model protein BSA. Each sample was cut into membrane strips of a certain size, placed in a BSA solution (0.5 mg·mL), incubated at 37°C for 5 h, stained with BCA protein reagent, and then measured at 562 nm with an enzyme reader to measure the absorbance and calculate the protein adsorption of the sample using the standard curve.

[0057] (6) Preparation of colloidal gold test paper

[0058] Colloidal gold-labeled goat anti-human IgG was used as an immunoassay marker and rabbit anti-goat IgG was used as a quality control line antibody and sprayed on the solid phase carrier membrane. The binding pad, sample pad, PVDF membrane and absorbent paper were sequentially pasted on the PVC bottom plate to assemble an immunochromatographic test strip.

[0059] In order to make the contents of the present invention more clearly understood, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0060] Examples 1-4 and Comparative Example 1 are used to illustrate the preparation of PVDF membranes.

[0061] Embodiment 1:

[0062] The high molecular weight hydrophilic additive PVP K90 PEG 600 Blend with PVDF powder, add solvent and stir at 60℃ for 24h, then degas to obtain uniform casting solution for use. K90 The content is 4%, PEG 600 The content is 2%, the PVDF content is 16%, and the solvent N-methylpyrrolidone content is 78%. Then the membrane is prepared by phase separation, wherein the coagulation bath is a 60% N-methylpyrrolidone solution, the temperature is 60°C, the air temperature is 25°C, the air humidity is 60%, and the membrane is dried at room temperature; 1g Tween 20 and 5g glycerol are weighed and dissolved in 96g deionized water, mechanically stirred at 37°C, and the PVDF membrane prepared in the above steps is immersed in the solution for 8h. Then the membrane piece is taken out and dried naturally to obtain a PVDF membrane.

[0063] Embodiment 2:

[0064] The operation steps of this embodiment are the same as those of embodiment 1, except that the porogen PVP is added. K90 The content of is different from that of solvent N-methylpyrrolidone.

[0065] The high molecular weight hydrophilic additive PVP K90 PEG 600Blend with PVDF powder, add solvent and stir at 60℃ for 24h, then degas and filter to obtain uniform casting solution for use. K90 The content is 6%, PEG 600 The content is 2%, the PVDF content is 16%, and the solvent N-methylpyrrolidone content is 76%. Then, the membrane is prepared by phase separation, wherein the coagulation bath concentration is 60% N-methylpyrrolidone solution, the temperature is 60°C, the air temperature is 25°C, the air humidity is 60%, and the membrane is dried at room temperature; 1g Tween 20 and 5g glycerol are weighed and dissolved in 96g deionized water, mechanically stirred at 37°C, and the PVDF membrane prepared in the above steps is immersed in the solution for 8 hours. Then the membrane piece is taken out and dried naturally to obtain a PVDF membrane.

[0066] Embodiment 3:

[0067] The operation steps of this embodiment are the same as those of embodiment 1, except that the porogen PVP is added. K90 The content of is different from that of solvent N-methylpyrrolidone.

[0068] The high molecular weight hydrophilic additive PVP K90 PEG 600 Blend with PVDF powder, add solvent and stir at 60℃ for 24h, then degas and filter to obtain uniform casting solution for use. K90 The content is 8%, PEG 600 The content is 2%, the PVDF content is 16%, and the solvent N-methylpyrrolidone content is 74%. Then, the membrane is prepared by phase separation, wherein the coagulation bath concentration is 60% N-methylpyrrolidone solution, the temperature is 60°C, the air temperature is 25°C, the air humidity is 60%, and the membrane is dried at room temperature; 1g Tween 20 and 5g glycerol are weighed and dissolved in 96g deionized water, mechanically stirred at 37°C, and the PVDF membrane prepared in the above steps is immersed in the solution for 8h. Then the membrane piece is taken out and dried naturally to obtain a PVDF membrane.

[0069] Example 4

[0070] The operation steps of this embodiment are the same as those of embodiment 1, except that the porogen PVP is added. K90 The content of is different from that of solvent N-methylpyrrolidone.

[0071] The high molecular weight hydrophilic additive PVP K90 PEG 600 Blend with PVDF powder, add solvent and stir at 60℃ for 24h, then degas and filter to obtain uniform casting solution for use. K90 The content is 10%, PEG 600The content is 2%, the PVDF content is 16%, and the solvent N-methylpyrrolidone content is 72%. Then, the membrane is prepared by phase separation, wherein the coagulation bath concentration is 60% N-methylpyrrolidone solution, the temperature is 60°C, the air temperature is 25°C, the air humidity is 60%, and the membrane is dried at room temperature; 1g Tween 20 and 5g glycerol are weighed and dissolved in 96g deionized water, mechanically stirred at 37°C, and the PVDF membrane prepared in the above steps is immersed in the solution for 8 hours. Then the membrane piece is taken out and dried naturally to obtain a PVDF membrane.

[0072] Comparative Example 1

[0073] The difference between Comparative Example 1 and Example 1 is that the surfactant Tween 20 is not added, and the other operating steps are the same.

[0074] The high molecular weight hydrophilic additive PVP K90 PEG 600 Blend with PVDF powder, add solvent and stir at 60℃ for 24h, then degas to obtain uniform casting solution for use. K90 The content is 4%, PEG 600 The content is 2%, the PVDF content is 16%, and the solvent N-methylpyrrolidone content is 78%. Then the membrane is prepared by phase separation, wherein the coagulation bath is a 60% N-methylpyrrolidone solution, the temperature is 60°C, the air temperature is 25°C, the air humidity is 60%, and the PVDF membrane is dried at room temperature.

[0075] Example 5

[0076] In this example, the membranes prepared in Examples 1-4 and Comparative Example 1 were pasted on a PVC base plate, and a tetrafluoroethylene capillary with an inner diameter of 0.5 mm was used to inject the rabbit anti-sheep IgG antibody of the quality control line at a rate of 1 μL·cm -1 The specification was sprayed on the quality control line area of ​​the test strip and dried in a 37°C oven; the colloidal gold-labeled goat anti-human IgG protein solution was sprayed at 4 μL·cm -1 The specifications are sprayed on the treated conjugate pad; then the sample pad, conjugate pad, membrane, and absorbent paper are sequentially pasted on the PVC base plate, and each part should maintain an overlap of 2-3mm to assemble an immunochromatographic test strip.

[0077] SEM characterization of membrane surface and cross section

[0078] Figure 1 This is a scanning electron microscope image of a commercial film. When the surface is magnified 1k times, large holes are observed on the surface; when the cross section is magnified 400 times, the structure shows a combination of symmetrical network and continuous structure.

[0079] Figure 2This is a scanning electron microscope image of Example 1. When the surface is magnified 500 times, large pores are observed on the surface, but the number of pores is small; when the cross section is magnified 500 times, the structure presents a combination of symmetrical honeycomb and continuous shapes.

[0080] Figure 3 This is a scanning electron microscope image of Example 2. After the surface is magnified 500 times, large holes are observed on the surface, and it can be found that the number of openings is greater than that of Example 1; after the cross section is magnified 500 times, the structure presents a combination of symmetrical honeycomb and continuous shapes, and the connectivity is good.

[0081] Figure 4 This is a scanning electron microscope image of Example 3. After the surface is magnified 500 times, large holes are observed on the surface, with the largest number of open holes; after the cross section is magnified 500 times, the structure presents a combination of symmetrical honeycomb and continuous shapes, and the connectivity is good.

[0082] Figure 5 This is a scanning electron microscope image of Example 4. After the surface is magnified 500 times, large holes are observed on the surface, and the number of openings is less than that of Example 4; after the cross section is magnified 500 times, the structure shows a large number of spherical crystals and giant holes, and the connectivity is good.

[0083] By comparing the electron microscope photos, it can be seen that different proportions of additives are used in the present invention. By adjusting the proportion of the additives, the pore size and pore structure of the PVDF membrane can be effectively adjusted, ensuring a regular shape, continuity and good connectivity, which is beneficial to improving the lateral flow efficiency of the test sample in the PVDF membrane.

[0084] The comprehensive performance of the membrane is evaluated by testing the tensile strength, elongation at break, pore size, porosity, capillary flow time and protein adsorption of the obtained flat membrane. The formula of the embodiment and the test results of various properties are shown in the following tables:

[0085] Table 1 Test results of Examples 1-4

[0086]

[0087] Pore ​​size distribution characterization

[0088] From Table 1 and Figure 6 It can be seen that the pore size distribution of the PVDF membrane prepared by the present invention is uniform. The pore size distribution is 4-12 μm. Comparing the differences between different embodiments, it is obvious that the use of PVP K90 Micron-scale macropores can be prepared, and as the porogen content increases, the pore size of the prepared membrane also increases.

[0089] Mechanical properties test

[0090] The mechanical properties test results of the PVDF membranes prepared in the above examples are shown in Table 1 and Figure 7 With PVP K90 As the proportion of increases, the tensile strength and elongation at break of the film all decrease. This is because the addition of additives changes the structure of the film, forming more holes and resulting in a decrease in mechanical strength.

[0091] Porosity characterization

[0092] From Table 1 and Figure 8 It can be seen that the porosity of the PVDF membranes prepared in Examples 1-4 shows an increasing trend. This is because PVP K90 As a polymer additive, with the increase in dosage, more porogens participate in the film-forming process, resulting in an increasing trend in the porosity of the film.

[0093] Capillary migration rate test

[0094] From Table 1 and Fig. 9 It can be seen that the capillary flow time of the PVDF membrane prepared in Examples 1-4 increases with the addition of the additive PVP. K90 The increase in the length of the membrane increases the pore size, which is due to the addition of porogens, which increases the pore size of the membrane and allows water molecules to enter the membrane better, which helps chromatography. In addition, PVP K90 It is a hydrophilic additive that can be present in the membrane to enhance the hydrophilicity of the membrane, shortening the capillary flow time. However, in Example 1, no surfactant modification was used, resulting in insufficient hydrophilicity of the membrane and no chromatographic effect. Fig.10 As shown, according to PVP K90 The relationship between additive content and capillary flow time is fitted into the empirical equation:

[0095] y=-3.25x 3 +68.125x 2 -485.75x+1365

[0096] Among them, x is the additive content and y is the capillary flow time, which intuitively expresses the relationship between the two.

[0097] Protein adsorption test

[0098] From Table 1 and Fig.11 It can be seen that the films prepared in Examples 1-4, with the addition of PVP K90 The increase in content leads to a decrease in protein adsorption. This is because the hydrophilicity of the membrane is enhanced, which is not conducive to protein adsorption. In addition, the increase in the pore size of the membrane reduces the contact area between the membrane surface and the protein, so the protein adsorption decreases.

[0099] Colloidal gold test strips

[0100] from Fig.12It can be seen that when 0.1 mol / L PBS buffer solution is used as the detection solution, when the PBS buffer solution carries the colloidal gold-labeled goat anti-human IgG and is chromatographed to the position of the rabbit anti-goat IgG, the two antibodies specifically bind to each other, causing the test strip to develop color at the designated position. When the membranes prepared in Examples 1-3 are applied to the test strips, they all have the ability to develop color, while the test strips of Example 4 and Comparative Example 1 do not develop color. For Example 4, the enhancement of the hydrophilicity of the membrane is not conducive to the adsorption of antibody proteins. When the content of the additive is high, the amount of protein adsorption is too low, resulting in the test strip not developing color; while the pores and surface of the membrane of Comparative Example 1 do not contain surfactants, and the membrane chromatographic capacity is insufficient, resulting in the inability of the antibody to specifically bind, and the test strip does not develop color.

Claims

1. A PVDF polymer lateral chromatography membrane, characterized in that: The PVDF polymer lateral chromatography membrane has porous characteristics, with a porosity of 50-82% and an average pore size of 4-8 μm. The PVDF base membrane has a tensile strength of at least 0.3 MPa and a breaking elongation of 10%, a porosity of at least 80%, and a capillary migration time of at least 180 s.

2. The PVDF polymer lateral flow membrane according to claim 1, characterized in that The chromatographic membrane also contains surfactants in its pores and / or on its surface.

3. The PVDF polymer lateral chromatography membrane according to claim 1, characterized in that The surfactant includes one or more of Tween 20, Tween 60, Tween 80, sodium dodecyl sulfate, polyethylene glycol octylphenyl ether, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium lauroyl sarcosinate, sodium methyl cocoyl taurate, and sodium polyoxyethylene lauryl ether sulfate in any weight ratio.

4. The method for preparing the PVDF polymer lateral chromatography membrane according to claim 1, characterized in that: The following steps are involved: Step 1: preparing casting solution: mixing PVDF powder and porogen, then adding solvent to dissolve to obtain uniform casting solution; Step 2: The casting solution is scraped by a desktop scraping machine, and then a porous membrane is formed by phase inversion in a coagulation bath; Step 3: The obtained porous membrane is placed in a solution containing a surfactant for immersion treatment, taken out and dried to obtain a chromatography membrane.

5. The preparation method according to claim 4, characterized in that: The casting solution comprises 10%-25% PVDF powder, 4%-12% porogen and 63-86% solvent by mass; the preferred range is 15%-20% PVDF powder, 6%-10% porogen and 75-80% solvent.

6. The preparation method according to claim 4, characterized in that: The porogen includes PVP K30 、PVP K60 、PVP K90 , PEG, glycerol or any combination thereof in any weight ratio; the molecular weight range of the PEG is 200-20000; the PVP K90 The content and the capillary migration time of water on the membrane surface are calculated by the following formula: y=-3.25x 3 +68.125x 2 -485.75x+1365, where x is the additive content and y is the capillary flow time.

7. The preparation method according to claim 4, characterized in that: The solvent includes but is not limited to one or any combination of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, triethyl phosphate, cyclohexanone, and acetone; the scraper thickness during the film scraping process is 100-500 μm, the film scraping temperature is 20-60° C., and the humidity is 20-98%.

8. The preparation method according to claim 4, characterized in that: The temperature of the coagulation bath is 30-90°C, and the solvent concentration is 20%-80%.

9. The preparation method according to claim 4, characterized in that: The solution containing the surfactant has a surfactant concentration of 0.1%-5% and also contains 2-10% glycerol, and the soaking time is 1-8 hours.

10. Use of the PVDF polymer lateral flow membrane according to claim 1 in an in vitro diagnostic test strip.

Citation Information

Cited By

  • Low-background high-protein combined polyvinylidene fluoride transfer printing film as well as preparation and application thereof

    CN121159903A